Post-study work for international graduates in Australia: opportunity to enhance employability, get a return on investment or secure migration?. (19th October 2020) - Tran, Ly Thi; Rahimi, Mark; Tan, George; Dang, Xuan Thu; Le, Nhung
ABSTRACT: In a competitive international education market, the opportunity to gain post-study work experience in the host country is one of the key drivers of international students' decision making and critical to education export, especially in top destination countries, such as Australia, Canada, the UK and US. Understanding the impacts of post-study work for international graduates is crucial for both host countries' international student recruitment and employment agendas and their ethical commitment to delivering on promise to the international cohort. Drawing on analysis of government policies and in-depth interview data, this study provides evidence about the effects of the post-study work policy in Australia. The overarching view from international graduates indicates that the temporary graduate visa does not seem to provide them with a competitive advantage in the Australian labour market as employers either are unclear about this visa or hesitate to recruit those on this visa. However, the visa brings multiple side benefits, including the chance to round off their employability skills, improve their English proficiency, and get a return on investment in overseas study. Many international graduates see the post-study work visa as a pathway to permanent residency despite the fact that visa reforms have broken the direct education-migration pathway.